2001
DOI: 10.1136/ard.60.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic stage of osteoarthritis or sex of the patient does not predict one year outcome after total hip arthroplasty

Abstract: Objective-To investigate whether patients with severe radiographic osteoarthritis (OA) have a diVerent outcome at one year after total hip replacement than patients with moderate radiographic OA. To investigate sex related diVerences in preoperative radiographic and self reported status and in postoperative outcome. Methods-184 patients (96 women) with a mean age at surgery of 71.4 years (50-92), with primary OA of the hip were investigated preoperatively and six and 12 months postoperatively with two self adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 27 publications
4
50
0
Order By: Relevance
“…First, we did not obtain any objective measures of the severity of hip arthritis to see whether lower baseline PROM scores were matched by more severe radiographic findings in women. Some previous studies suggest that the grade of radiographic OA is unrelated to self-rated pain and function (WOMAC scores), at least for moderate to severe OA [31], whereas others show a relationship between radiographic and clinical variables [5,10]. Second, this study was conducted in Switzerland; differences between countries in their healthcare systems or social structure might govern whether gender differences in baseline PROMs are observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we did not obtain any objective measures of the severity of hip arthritis to see whether lower baseline PROM scores were matched by more severe radiographic findings in women. Some previous studies suggest that the grade of radiographic OA is unrelated to self-rated pain and function (WOMAC scores), at least for moderate to severe OA [31], whereas others show a relationship between radiographic and clinical variables [5,10]. Second, this study was conducted in Switzerland; differences between countries in their healthcare systems or social structure might govern whether gender differences in baseline PROMs are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, gender may have an influence on the interpretation of patientrated outcomes when judging the success of surgery. Many [18,30,32] but not all [31] studies have shown that women have higher pain levels and worse function when they present for surgery for the treatment of degenerative musculoskeletal conditions. However, it is unclear whether this necessarily translates into a worse overall outcome after surgery or a lower level of satisfaction with treatment.…”
Section: Introductionmentioning
confidence: 99%
“…According to certain studies, the relationship between radiographic findings and pain and function is weak (18 -20). It has been suggested that the preoperative radiographic grade does not influence the clinical outcome 1 year after THA (20). Consequently, it has been proposed that symptoms, and not the degree of radiographic change, should provide the indication for surgery (6,20).…”
Section: Indication For Total Hip Arthroplastymentioning
confidence: 99%
“…Consequently, we refrained from computing pooled z-scores for these studies. We pooled two studies concerning patients with knee or hip OA in clinical settings (data from hip and knee patients were not presented separately in these studies) [29,30], three studies on patients with knee OA in clinical settings [31][32][33], two studies on patients with knee or hip OA, admitted or scheduled for TKA or THA (data from hip and knee patients were also not presented separately in these studies) [34,35], 19 studies on patients with knee OA admitted or scheduled for TKA [25,26,28,33,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and 23 studies on patients with hip OA admitted or scheduled for THA [26,28,36,[39][40][41][42][43][44][45][46][48][49][50][51][52][53][54][55]…”
Section: Data Synthesis and Presentationmentioning
confidence: 99%
“…Of the 40 studies we included, one study concerned patients in the general population [61] (223 patients), three studies concerned community living elderly [27,62,63] (in total 133,358 patients), one study concerned patients in a primary care setting [64] (195 patients), five studies concerned patients in clinical settings [29][30][31][32][33] (in total 1407 patients) and thirty studies concerned patients with OA admitted or scheduled for total arthroplasty (in total 5191 patients admitted for TKA [25,26,28,33,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]65] and 4236 patients admitted for THA [26,28,36,[39][40][41][42][43][44][45][46][48][49][50][51][52][53]…”
Section: Characteristics Of the Study Populationsmentioning
confidence: 99%